Short-Term Prognostic Value of Strain Echocardiography in Patients with STEMI - Batmyagmar Khuyag; Surenjav Chimed; Amarjargal Baldanndorj; Lkhagvasuren Zundui; Narantuya Davaakhuu (Central Asian Journal of Medical Sciences, 2017)
Objectives: Left ventricular (LV) systolic function is major predictor of outcome after acute myocardial infarction (AMI). In recent years, speckle-tracking echocardiography (STE) derived strain measurement has been demonstrated to directly reflect myocardial deformation patterns and to be superior to conventional echocardiographic measurements. Our study aimed to reveal the prognostic value of strain parameters for 30-day mortality in patients with ST elevation myocardial infarction (STEMI) after primary percutaneous coronary intervention (PCI). Methods: We prospectively included patients with STEMI after primary PCI treatment. The primary endpoint was 30-day mortality. 2D STE was used to determine LV strain parameters. Results: 414 patients were selected. 30-day mortality occurred in 15 patients (3.6%). LV global longitudinal strain (GLS) was significantly impaired in the 30-day mortality group compared with survivors (-8.0±2.6% vs. -15.4±3.8%, p<0.001). Multivariate regression revealed that LV GLS was independently associated with 30-day mortality (OR 1.71, 95% CI 1.23-2.38, p<0.001). Adding GLS into the clinical and echocardiographic model improved model performance. Conclusion:The LV GLS parameter is an independent predictor of 30-day mortality in patients with STEMI after primary PCI treatment. Adding LV GLS into the prediction model improved its predictive performance.